Assessment of Irrigation Access, Challenges and Opportunity in Wolaita, Kembata Tembaro and Hadiya Zones of Snnppr, Ethiopia - Yidnekachew Alemayehu; Seifu Tesfa Yohannes (International Journal of Rural and Regional Development, 2025)
In the Wolaita, Kembata Tembaro, and Hadiya zones, this study evaluated irrigation access and the difficulties that come with it. The data in this study were analyzed using an econometric model in addition to descriptive statistics. The study region yielded both primary and secondary data. For this investigation, the multi-stage sampling technique was used. Using a pre-tested questionnaire, 139 sample household heads were chosen at random and questioned. To support the formal data, informal techniques including focus groups and key informant interviews were used. The results of analysis indicated that about 16.5% those who have their own irrigation water harvesting technology whereas 83.5% did not have this technology. The majority (79.1%) of the sample respondents were using modern irrigation type whereas the remaining 20.1% were use traditional irrigation type. Of the sample 57.6% respondents indicated access to water which limit the area to cultivate in any season of the year whereas 42.4% did not agree. Attitude toward the use of irrigation by the male and female sample household head has no significant mean difference between them. As access to irrigation increase, the probability of farmers having own irrigation water harvesting technology decrease by 48.4% which is negatively significant at 5% of significance level. High input costs, lack of money and labor shortage were the main factors in affecting irrigation use of sample respondents in the study area. Therefore, an intervention is needed to improve irrigation facility, infrastructural development and canal maintenance for efficient irrigation water utilization to enhance production and productivity in the study area.
Keywords: Descriptive statistics; constraints; econometric model; irrigation